Strategic Planning and Service Delivery at Kenya Power Headquarters in Kenya - Wanjiku, Elizabeth Muthoni; Njuguna, Videlis Njeri (Journal of Business and Strategic Management, 2024)
Purpose: The major objective was to establish how strategic planning affected service delivery in KenyaPower. The study was based on the theory of contingency. Methodology: The study employed descriptive design. The target population consisted of 247 managers at various levels (low-level, mid-level and senior-level) from 11 departments at headquarters of Kenya Power. This study employed stratified random sampling techniques to select sample size of 114 staff. The study used primary data collection utilizing both open and closed-ended questionnaire. The questionnaires were distributed and collected using a drop-off and pick-up later method. The quantitative analysis used descriptive techniques such as frequency, percentage, standard deviations and means. The research also employed linear regression to examine the effect of strategic planning on service delivery. Findings: The research established that strategic planning (β=0.787; p=0.000) had substantial effects on service delivery at KenyaPower. Research concluded that strategic plannings have significant effects on delivery of services in Kenya Power. Unique Contribution to Theory, Policy and Practice: The study recommended that Kenya Power's executives should implement training programs for its workers. This would provide employees with the essential skills and abilities needed to improve the quality of service delivered to clients. Kenya Power should also make sure that its goals and objectives are clear and understandable to employees at every level by use of efficient communications.